2004
DOI: 10.1016/j.febslet.2004.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic evidence related to substrate‐assisted catalysis of family 18 chitinases

Abstract: The hydrolytic reaction of family 18 chitinase has been considered to occur via substrate assisted catalysis. To kinetically investigate the enzyme reaction mechanism, we synthesized compounds designed to reduce the polarization of the carbonyl in N-acetyl group, GlcNAc-GlcN(TFA)-UMB (2) and GlcNAc-GlcN(TAc)-UMB (3). Kinetic parameters in the hydrolysis of these compounds by chitinase A from Serratia marcescens (ChiA) were compared with those from the hydrolysis of (GlcNAc) 2 -UMB (1). The k cat of 2 was 3.4% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Several retaining glycosyl hydrolases that break down chitin such as GH18 chitinases follow a substrate‐assisted catalytic mechanism in which the 2‐acetamido group of the substrate acts as the nucleophile . Allosamidin mimics the oxazolinium ion intermediate and inhibits most chitinases of this family .…”
Section: Discussionmentioning
confidence: 99%
“…Several retaining glycosyl hydrolases that break down chitin such as GH18 chitinases follow a substrate‐assisted catalytic mechanism in which the 2‐acetamido group of the substrate acts as the nucleophile . Allosamidin mimics the oxazolinium ion intermediate and inhibits most chitinases of this family .…”
Section: Discussionmentioning
confidence: 99%
“…The catalytic mechanism of family-18 chitinases involves protonation of the leaving group by an absolutely conserved glutamic acid (equivalent to Glu315 of Serratia marcescens chitinase A), followed by substrate distortion into a 'boat' conformation at subsite À1 and the stabilisation of an oxazolinium intermediate by the sugar N-acetamido group. The resultant bond cleavage yields the retention of anomeric configuration in the products (Armand et al, 1994;Fukamizo et al, 2001;Honda et al, 2004;Sasaki et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Dennis et al (2006); Honda et al (2004); Langley et al (2008); Ling et al (2009); Markovic‐Housley et al (2000); Morley et al (2009); Reid et al (2007); Stummeyer et al (2005)…”
Section: What Replaces a Typical Catalytic Base/nucleophile?mentioning
confidence: 99%
“…The presence of a nucleophile in retaining GHs is important as it directly attacks the anomeric center to form a glycosyl–enzyme intermediate. However, by both detailed kinetic and X‐ray structural studies, the carbonyl oxygen of the 2‐acetamide group in the substrate of GH‐18 chitinases (Honda et al, 2004), GH‐20 hexosaminidases (Langley et al, 2008), GH‐56 hyaluronidases (Markovic‐Housley et al, 2000), GH‐84 O ‐GlcNAc‐ases (Dennis et al, 2006), GH‐85 endo ‐β‐ N ‐acetylglucosaminidases (Ling et al, 2009; Rich and Withers, 2009), and GH‐103 lytic transglycosylases (Reid et al, 2007) has been shown to act as the nucleophile to form an oxazoline intermediate (Fig. 5).…”
Section: What Replaces a Typical Catalytic Base/nucleophile?mentioning
confidence: 99%